2018
DOI: 10.1016/j.psyneuen.2018.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination exposure and DNA methylation of stress-related genes in Latina mothers

Abstract: Latina mothers, who have the highest fertility rate among all ethnic groups in the US, are often exposed to discrimination. The epigenetic changes related to this discrimination are largely unknown. This study is the first to explore the relationship between discrimination and DNA methylation of stress regulatory genes in Latinas. Our sample was Latina women (n = 147) with a mean age of 27.6 years who were assessed at 24-32 weeks' gestation (T1) and 4-6 weeks postpartum (T2) and reside in the U.S. Blood was co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 57 publications
(61 reference statements)
0
27
0
Order By: Relevance
“…In addition, our sample was relatively homogenous consisting primarily of low-income Dominican middle-aged and older women. This is important to consider as recent studies have found that younger Latina women report a lower prevalence of everyday discrimination (approximately 41%-44%) than what was observed in the middle-aged and older women included in the present study (Otiniano Verissimo et al, 2013;Santos et al, 2018). Not surprisingly, the majority of women in this study were post-menopausal.…”
Section: Limitationsmentioning
confidence: 49%
See 1 more Smart Citation
“…In addition, our sample was relatively homogenous consisting primarily of low-income Dominican middle-aged and older women. This is important to consider as recent studies have found that younger Latina women report a lower prevalence of everyday discrimination (approximately 41%-44%) than what was observed in the middle-aged and older women included in the present study (Otiniano Verissimo et al, 2013;Santos et al, 2018). Not surprisingly, the majority of women in this study were post-menopausal.…”
Section: Limitationsmentioning
confidence: 49%
“…For instance, a cross-sectional study of young Latino men and women found that 60.2% of Latino men and 41.2% of Latina women reported experiencing everyday discrimination (chronic, but often minor experiences of unfair treatment that commonly occur in day-to-day interpersonal interactions; Otiniano Verissimo et al, 2013). In addition, in a sample of 150 pregnant Latina women (mean age ¼ 27.6 years), investigators found approximately 44% of participants reported experiencing some form of everyday discrimination in their lifetimes (Santos et al, 2018). A recent systematic review of 33 studies found that perceived discrimination is consistently associated with a higher prevalence of depressive symptoms and substance use among Latinos across studies (Andrade et al, 2020).…”
mentioning
confidence: 99%
“…In immigrant women, acculturative stress is often accompanied by family separation, social and linguistic isolation, and discrimination [40]-salient contributors of perinatal depression among Mexican-American mothers [41]. The cumulative effects of these stressors on the relationship between maternal mental health and the child's gestational and early childhood experiences may alter not only the child's life course but the physiology of subsequent generations via biological (e.g., epigenetic) mechanisms [38,42,43] and interpersonal (e.g., parenting) processes [42]. The Latino paradox, wherein less acculturated Latinos experience better health outcomes than more acculturated Latinos, has been documented for maternal and child health: birth weights [44] and breastfeeding rates [45].…”
Section: Plos Onementioning
confidence: 99%
“…Several reviews have linked racial discrimination [ 21 , 49 , 50 ] with changes in various cortisol parameters, which in turn have been linked with poorer mental and physical health [ 51 , 52 ]. Deleterious changes in other biological processes such as heightened inflammation [ 22 ] and alterations in DNA methylation of stress-related genes [ 53 ] have been linked with discrimination in recent studies. Alterations in these stress-related biological processes offer a plausible link to negative changes in physical [ 54 , 55 ] and, mental health outcomes [ 51 , 56 ].…”
Section: Discussionmentioning
confidence: 99%